Does China Switch from its "Invite-in-Go-Out" Strategy Toward a "Block-and-Attack" Strategy"? Implications for Europe - Heiduk, Guenter; Szczypa, Agnieszka (Czy Chiny porzucą strategię "przyciągania i ekspansji" na rzecz strategii "utrudniania i ataku"? Wnioski dla Europy, 2010)
Over the last 30 years, China's growth has been considerably based on its opening-up strategy that firstly "invited" foreign investors and secondly fostered trade. The current economic crisis has put pressure and doubts on the future success of this strategy. China's government fears that the politically propagated growth rate of 8% is in danger. Furthermore, the extensive public investment in infrastructure and state-owned companies combined with private investment in real estate has created signs of a bubble economy that could burst in times of declining growth. China's new growth strategy seems to focus firstly on increasing private consumption and secondly on hampering foreign inflows of goods and capital, while at the same time supporting aggressive international market entry strategies of Chinese companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 339-348
Keywords: open economy; policy-oriented outwards; emerging markets; China